Factors influencing unclaimed properties in Shah Alam, Selangor - Muhammad Imran Mohd Zuhuri; Nur Syazwina Md Ibrahim; Nurul Amira Amat Amran; Nurul Aisyaa Syafiqa Mohd Zaki (2022)
This paper aimed to study the effect between lack of knowledge, heirs awareness and complex administration process towards unclaimed properties among residents in Shah Alam, Selangor. This study reviewed the literature of past research of factors that influenced unclaimed properties in Shah Alam, Selangor. The main factor of unclaimed properties that was used in this study was to analyse residents' knowledge, awareness and complex administration process. We used a survey questionnaire to collect 384 valid responses from the residents in Shah Alam, Selangor. These collected data were analysed using SPSS version 25 and the result gathered through Pearson’s Correlation Coefficient and Multiple Regression. The findings revealed the knowledge, awareness and complex administration process with significant influence on residents in Shah Alam, Selangor. The implication from this study is for the resident who is the resident who is having knowledge, having awareness and having a complex administration process. Finally, the result shows that a lack of the knowledge, heirs awareness and complex administration process are the factors that influence the most unclaimed properties among residents in Shah Alam, Selangor. Keywords: unclaimed properties, lack of knowledge, heirs awareness, complex administration, residents of Shah Alam